Chaihu Shugan prevents cholesterol gallstone formation by ameliorating the microbiota dysbiosis and metabolic disturbance in mice - Wang, Wei; Zhang, Kun; Liu, Bin; Zhou, Tong; Tang, Yu; Li, Yuliang (Frontiers in Pharmacology, 2024)
Cholesterol gallstone (CGS) is a biliary tract disorder requiring treatment in approximately 20% of patients. The efficacy of Chaihu Shugan in preventing CGS recurrence after successful treatment remains uncertain. We examined the in vivo preventive efficacy of Chaihu Shugan using a CGS mouse model and used multi-omics to study the interplay between gut microbiota, metabolism, and gene expression. The intestinal microbiota was severely dysregulated during the formation of CGS, showing a marked decrease in the abundance of beneficial microbiota, especially Lactobacillus and Akkermansia. Chaihu Shugan prevented CGS formation by restoring the composition of the gut microbiota and reversing the metabolic disturbances caused by dysbiosis. This preventive effect of Chaihu Shugan was paralleled by changes in the expression of metabolism-related genes in the liver. A network pharmacology analysis of Chaihu Shugan revealed that obacunone may be the key active metabolite in regulating bile acid metabolism. Multi-omics and correlation analyses elucidated the interplay between gut microbiota, metabolism, and gene alterations in the dose-dependent effect of Chaihu Shugan. Our data show that Chaihu Shugan can prevent CGS and indicate its mechanisms of action.